Pengaruh Kompetensi Penempatan Kerja Terhadap Kinerja Karyawan di Balai Pengelola Transportasi Darat (BPTD) Kelas III Bengkulu - Syaputra, Riken; Al Hidayat, Rahmat; Yuningsih, Siti (Jurnal Administrasi Bisnis Nusantara, 2026)
This research aims to find out and understand the Influence of Work Placement Competence on Employee Performance at the Land Transportation Management Center (BPTD) Class III Bengkulu. The type of research used in this research is a quantitative approach. The population in this study is all employees at the Land Transportation Management Center (BPTD) Class III Bengkulu. The sample used in this study was 100 respondents taken using the distribution of questionnaires and data analysis techniques. The data analysis used to test the hypothesis is the simple linear regression analysis and the t test (partial test) which is processed using statistical calculations through the application (SPSS) version 25. The results of this study show that Work Placement Competency has a positive and significant effect on employee performance at the Land Transportation Management Center (BPTD) Class III Bengkulu which is proven by the regression coefficient value (Work Placement Competency X) of 0.075 and the calculated t value of 2.824 with a significant value of 0.006 < 0.05. This means that this explains that if Work Placement Competency has a positive and significant effect on employee performance at the Land Transportation Management Center (BPTD) Class III Bengkulu, which shows when the performance of employees who can manage work motivation, with expertise that is able to improve the quality of the company.